(untitled) (International Journal of Biology and Chemistry, 2025)
Humic substances (HS) possess significant physiological activity and play a crucial role in enhancing soil properties and plant productivity. This study is devoted to the determination of the content of natural radionuclides in humate-containing samples obtained from natural raw materials of Kazakhstan. Five samples, including both solid and liquid fertilizers, were prepared and analyzed. Key parameters such as elemental composition, content of carboxyl and phenolic groups, and the yield of free humic acids were determined. The concentrations of uranium-238, uranium-234, thorium-232, thorium-230, thorium-228, polonium-210, and lead-210 isotopes were measured using alpha-spectrometric and alpha-beta radiometric methods. Results indicated that the liquid fertilizer exhibited the lowest radionuclide activities, while the solid samples showed varying levels of radioactive isotopes, with the highest activity recorded in sample A2. Nonetheless, the specific activities of all measured radionuclides complied with the national radiation safety standards (SanPiN 2.6.1.2523-09), confirming the fertilizers’ safety for agricultural use. This work highlights the importance of radiation monitoring in fertilizers and the potential of humate-containing materials as environmentally friendly agricultural enhancers. The findings contribute to the development of sustainable agricultural practices through the safe utilization of natural organomineral fertilizers derived from local raw materials. Keywords: Humic substances, natural radionuclide, fertilizers, uranium series, activity concentration